Farmlend: a novel method for tackling agricultural waste in crop production - finance & valuation - Putten, Thibaud Ludovicus Van Der (2022)
Students were challenged by the Building Companies Based on Science Field Lab (FL) to investigate a scientific discovery and develop a business strategy with the objective of launching an enterprise. Throughout the FL, the students investigated a subject and its implications for society. They then pursued market research, sizing, and a study of all parties involved to identify a fresh and unique solution to the problem. Later on, students created a financial analysis in which they identified fundraising requirements, prospective alliances, essential skills, valuation, and probable exit scenarios. This final paper contains all of the latter materials concerning the financing